Molecular confirmation of Sarcocystis fayeri in a donkey - Coultous, Robert M.; Raftery, Alexandra G.; Shiels, Brian R.; Sutton, David G.M.; Weir, William (Veterinary parasitology, 2017)
•Molecular confirmation of Sarcocystis fayeri in a donkey for the first time.•Phylogenetic analysis of sequence demonstrates placement in S. fayeri clade.•The donkey as a potential intermediate host has implications for epidemiology of the parasite. Sarcocystis fayeri is a canine protozoan parasite with an equine intermediate host. Historically classified as an incidental pathogen, recent literature has described the toxic effects of Sarcocystis fayeri in human food poisoning, and highlighted potential involvement in equine neuromuscular disease. Until now, horses were believed to be the exclusive intermediate host. This study reports the first molecular confirmation of S. fayeri in a donkey, and gives rise to the consideration of donkeys being a potential reservoir for the parasite. This finding is of particular importance in understanding the epidemiology of this disease.